Tracing the Roots: The Historical and Linguistic Legacy of Sanskrit In Ayurveda - Dr Sukhdevsinh Kamariya; Prof. Dr. Sreekanth V.M; Mr. Tejaskumar Vyas (The Bioscan, 2026)
Background: The Ayurveda traditional medical system of India is essentially influenced by the Sanskrit language which is not only the language, but also the philosophical and epistemological basis of the knowledge system. The major classical Ayurvedic texts, the Charaka Samhita and the Sushrata Samhita are written in Sanskrit, and within their vocabulary lie rich metaphysical, physiological and ethical connotations. The importance of Sanskrit to Ayurveda is however rarely addressed in modern literature despite its crucial role particularly as contemporary translation-based approaches towards Ayurveda evolve into vernacular translations and English ones. Objective & Methods: The purpose of this review is to uncover and examine historical and linguistic heritage of Sanskrit in the creation, transmission and conceptual framework of Ayurvedic knowledge. The qualitative narrative review approach was implemented based on secondary data sources, such as classical texts, peer-reviewed literature and linguistic analyses. Academic databases, institutional repositories and Sanskrit research centers were searched using specific Boolean search techniques to retrieve literature. Thematic analysis has been performed to know the patterns in the ways Sanskrit has affected Ayurvedic terminology, epistemology and pedagogy. Results & Conclusion: The findings indicate that Sanskrit has had a formative position in the development of Ayurvedic thought in terms of specific terminology, oral and written transmission and correspondence with classical Indian epistemologies. The Ayurvedic concepts of critical importance are endowed with their layers of meaning by Sanskrit etymology and grammar, and assist in a comprehensive perception of health. Sanskrit is no longer playing Ayurvedic training as a major part of contemporary training, but recent neo-revival movements are trying to highlight its still crucial role. To ensure the Ayurvedic authenticity but also to enhance its philosophical and clinical knowledge in modern situations, it is crucial to preserve and bring back Sanskrit.